Invasive Orbital Squamous Cell Carcinoma in a Patient with Multiple Myeloma - Narges Karrabi; Kiana Hassanpour; Noushin Afshar Moghaddam; Faezeh Khorasanizadeh; Sadid Hooshmandi; Amirreza Veisi (Case Reports in Ophthalmological Medicine)
Background. Orbital squamous cell carcinoma (SCC) is a rare entity. It is often a result of local invasion of SCC originating from the skin, nasopharynx, nasal cavity, paranasal sinuses, conjunctiva, lacrimal glands, or sac or less commonly occurs through hematogenous metastasis. Herein, we report a patient with orbital SCC with a history of multiple myeloma (MM). Case presentation. A 45-year-old woman with a history of MM in the past two years presented to our clinic complaining of gradual right eye proptosis for six months. The relative afferent pupillary defect was detected in the right eye on her examination. Ocular movements of the right eye were limited in all directions. Orbital magnetic resonance imaging demonstrated an infiltrative mass in the right orbit extended from the anterior to the orbital apex and the optic canal. The patient underwent debulking, and a histopathology examination revealed SCC results. No other secondary site was found to be the origin of the tumor. Result. The patient underwent chemotherapy and subsequent radiotherapy. To our knowledge, this is the first report of concomitant MM and primary orbital SCC.